Ride with Me - Ethnic Discrimination, Social Markets and the Sharing Economy - Jasper Dag Tjaden; Carsten Schwemmer; Menusch Khadjavi (European Sociological Review, 2018)
We study ethnic discrimination in the sharing economy using the example of online carpooling marketplaces. Based on a unique dataset of 16,624 real rides from Germany, we estimate the effects of drivers' perceived name origins on the demand for rides. The results show sizable ethnic discrimination. Further analyses suggest that additional information about actors in this market decreases the magnitude of ethnic discrimination. Our findings broaden the perspective of ethnic discrimination by shedding light on subtle, everyday forms of discrimination in social markets; inform ongoing discussions about ways to address discrimination in an era in which markets gradually move online; and respond to increasingly recognized limitations of experimental approaches to study discrimination.
Keywords: 330; ethnic discrimination; sharing economy; statistical discrimination; online markets; computational social science